Image of a Woman in the Proverbs of the Uzbek Language - Gulhayo Hamroyeva Yunus qizi (Genius Journals, 2022)
The article deals with the analysis of the proverbs of the Uzbek language devoted to the images of women in the gender aspect. There are studied, compared and revealed the specific features of the women images in these proverbs. The authors present their classification by the social status, role and functions of a woman in family and society.
Keywords: proverb; folk literature; uzbek language; gender